2022
DOI: 10.48084/etasr.5317
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Enhanced Performance of a Static Synchronous Compensator with a Super-Capacitor in Power Networks

Abstract: The use of a super-capacitor as a storage device integrated with a Voltage source converter-based shunt-connected Static Synchronous Compensator (STATCOM) is proposed for improving the STATCOM performance during sudden large disturbances in a power network. The super-capacitor was applied across the STATCOM capacitor during the disturbance condition. MATLAB simulations were carried out for the verification of a secondary function of the STATCOM like oscillation damping, transient stability improvement, and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The output signals of the controller V d1 and V q1 are converted from dq0 (V d1 and V q1 ) to abc (V aa , V ab and V ac ). The conversion from dq0 axes to abc axes is shown in ( 8)- (10). The signals V aa , V ab and V ac are the inputs to PWM used to control the six IGBT signals as given in Figure 8.…”
Section: Voltage Control Of Statcom Connected To the Microgrid At The...mentioning
confidence: 99%
See 2 more Smart Citations
“…The output signals of the controller V d1 and V q1 are converted from dq0 (V d1 and V q1 ) to abc (V aa , V ab and V ac ). The conversion from dq0 axes to abc axes is shown in ( 8)- (10). The signals V aa , V ab and V ac are the inputs to PWM used to control the six IGBT signals as given in Figure 8.…”
Section: Voltage Control Of Statcom Connected To the Microgrid At The...mentioning
confidence: 99%
“…The PI controller was adjusted at integral time constant (K i ) of 0.3 s and proportional gain (k p ) of 11. The outputs of the PI controller entered the dq0/abc device to convert the dq frame to abc frame as shown in ( 8)- (10). This device has a wt input with the same value as PLL.…”
Section: Voltage Control Of Statcom Connected To the Microgrid At The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two bidirectional DC-DC converters are used to create a novel STATCOM model with a hybrid energy storage system, and the performance of both the traditional STATCOM and the STATCOM with the hybrid energy storage system is compared (Renuka and Kesavarao, 2017). In Vaidya and Chandrakar (2022), STATCOM performance for transient condition was shown improved with super-capacitor energy storage system. In Zeng (2019), Fuzzy-PI-based controller is suggested for Static Synchronous Compensator, focusing on the demands of the power distribution network on transient load voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome showed that the SSSC controller based on RBFN is superior to the PI controller. For enhancing STATCOM performance during abrupt, significant disruptions, the usage of a super-capacitor with STATCOM is suggested in [11]. The control of damping of SSSC used in power systems is examined in this [12,13].…”
Section: Introductionmentioning
confidence: 99%